Samplers, videoclipes e letras: um debate sobre possibilidades de abordagem com músicas de rap na universidade - Passold, Gabriel (2017)
This research aims to discuss the approach of rap music in the university, analyzing concepts and principles used in some works that deal with the elements of lyrics, images of video clips and samplers, more often as representation, as well as some of the implications of this procedure, such as the valorization of the lyrics of the songs and the importance given to the role of the artist engaged in a possible emancipation of the ideologies of domination, in detriment of artists and / or works not adjusted to such concepts and theoretical-methodological principles. On the other hand, in our approach on rhyming, samplers, and in the case of music video clips, the images, we start from the assumption that music is not necessarily the representation of something but rather is formed by an aesthetic fabric with multiple interpretative possibilities. In this way, the research attempts to show some consequences of the interpretation of rap by the representative logic, such as the constitution of a kind of common sense based on some sociological and political hierarchies taken beforehand, as well as discussing other possibilities of thinking about the relationship between music, history and politics, as for example, by a community sense traced within aesthetic expressions.